Pengaruh Penerapan Elektronik Samsat terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor pada Kantor Samsat Jakarta Selatan - Maudy Sindia; Mawar Mawar (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
The application of E-Samsat in South Jakarta is considered as an alternative that has more advantages, even so there are still some taxpayers who do not fulfill their tax obligations, including in terms of paying motor vehicle tax. The purpose of this study is to determine the effect of the application of Electronic Samsat on the compliance of motor vehicle taxpayers at the South Jakarta samsat office. In this study using associative methods with a quantitative approach.. The results of this study explained that the application of E-Samsat had a significant and positive effect on motor vehicle taxpayer compliance at the South Jakarta samsat office. This can be seen in the results of the correlation coefficient test of 0.823 which can be interpreted to have a strong influence and the results of the determination coefficient test that the application of Electronic Samsat has an effect of 67.7% on the compliance of motor vehicle taxpayers at the South Jakarta samsat office.